2013
DOI: 10.3126/nepjoph.v5i2.8706
|View full text |Cite
|
Sign up to set email alerts
|

Prospective comparison of chilled versus room temperature saline irrigation in alcohol-assisted photorefractive keratectomy

Abstract: The use of room temperature saline irrigation during PRK appears to be safe and effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…This eye was still highly myopic after the surgery (−8.00 D) and had not developed haze. Significant haze 6 weeks after surgery was not found in any cPRK eyes, but in 16 % of LASEK eyes, which is similar to other cPRK and LASEK findings [13,25,27]. Significant haze following cPRK has been reported, but only in studies using old generation excimer lasers [11,16].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This eye was still highly myopic after the surgery (−8.00 D) and had not developed haze. Significant haze 6 weeks after surgery was not found in any cPRK eyes, but in 16 % of LASEK eyes, which is similar to other cPRK and LASEK findings [13,25,27]. Significant haze following cPRK has been reported, but only in studies using old generation excimer lasers [11,16].…”
Section: Discussionsupporting
confidence: 75%
“…Significant haze following cPRK has been reported, but only in studies using old generation excimer lasers [11,16]. Our results and the existing literature indicate that cPRK is more effective than LASEK in reducing initial significant haze [13,25,27]. To our knowledge, no studies have directly compared [18].…”
Section: Discussionsupporting
confidence: 60%
“…Many surgeons recommend that patients use eye-drops of cold artificial tears to reduce pain after surgery ( 23 , 24 ); however, another study reached the opposite conclusion. Neuffer et al ( 25 ) found no significant difference in the application of ice-cold or warm BSS during LASEK in a prospective, randomized single-blinded study.…”
Section: Discussionmentioning
confidence: 96%
“…In general, Excimer laser treatments may cause a significant increase in corneal temperature mainly due to the heat generation exceeding the heat dissipation during the laser treatment. 6 These thermal effects may cause tissue damage and potentially reduce the predictability of the refractive outcomes. 1 Usually cold balanced salt solution (BSS) is applied after the ablation procedure to reduce the postoperative increment of the ocular surface temperature (OST) which leads to several problems which by definition can be later introduced as haze and scattering.…”
Section: Palabras Clavementioning
confidence: 99%
“…1,3,4 The normal corneal surface temperature has been reported to range from 32.9 to 36 • C. 5 Under LASIK settings, when lid speculum has been applied, the dynamic heat balance shifts towards heat loss from the cornea to the surrounding cooler air and baseline corneal temperature (prior to initiating surgery) decreases to approximately 31 • C. When excimer laser is initiated, every single pulse adds heat to the cornea and contributes to the marginal increase in the local corneal temperature. 6 Laser refractive surgery is based on the sequential delivery of multiple laser pulses, with each pulse ablating a small amount of corneal tissue and in the process causing a marginal increase in the local corneal temperature around the laser spot. In general, Excimer laser treatments may cause a significant increase in corneal temperature mainly due to the heat generation exceeding the heat dissipation during the laser treatment.…”
Section: Palabras Clavementioning
confidence: 99%